Preliminary research on the effect of sutra chanting on oral and respiratory function: a comparison between expert sutra chanting buddhist priests and general buddhist priests in Japan - Edahiro, Ayako; Ura, Chiaki; Motohashi, Yoshiko; Shoji, Ryosho; Kaneko, Reisai; Ogawa, Yukan; Takase, Akinori; Nakano, Kousho; Okamura, Tsuyoshi (Frontiers in Aging, 2025)
IntroductionThere is limited prior research on the physiological effects of sutra chanting.MethodsThe health effects of sutra chanting were explored by comparing the oral and respiratory functions of Buddhist priests who are experts in sutra chanting with those of general Buddhist priests. In addition to basic characteristics, lifestyle variables, and general health status, participants underwent assessment of oral function and respiratory function by two certified dentists.ResultsCompared to general priests (n = 23), expert chanters (n = 49) were significantly higher in peak expiratory flow (PEF), forced vital capacity (FVC), and hyoid displacement (⊿HD). In the two multiple regression analyses which include PEF and FVC as the dependent variables, expert group demonstrated significantly better function.DiscussionConsidering its historical and cultural background, the idea of using sutra chanting has potential in a healthcare program for older people at risk of declining oral and respiratory functions.